Optimalization of Catfish Cultivation in Gunung Sarik, Kuranji, Padang: Catfish Cultivation - imtihan, iim; mayasari, lisa; Aryzegovina, Reffi; Endryeni; Safrika, Mulyadi (Community Development Journal, 2025)
Catfish is one of the freshwater fish commodities that has high economic value and is very potential to be developed in Indonesia, especially in Padang, West Sumatra. Choosing the righ location for catfish enlargement cultivation is one of the key factors for catfish enlargement. Gunung Sarik in Padang is one location that has the potential to develop a catfish cultivation business. The purpose of this community service activity is to optimize existing resources by utilizing the strengths and opportunities owned by the Gung Sarik catfish cultivation group. The method of implementation service activities consists of lectures, demonstrations, practice and mentoring. The results of this community service activity are (1) the Gunung Sarik catfish cultivation group can empower the potential of land in catfish cultivation better; (2) the Gunung Sarik catfish cultivation group can produce natural feed independently and has slowly been free from dependence on factory feed; (3) the Gunung Sarik catfish cultivation group can prepare good business financial reports in accordance with generally applicable Financial Accounting Standards. Furthermore, another advantage of this community service activity can increase community income by creating new jobs.